2015
DOI: 10.1039/c4dt03075c
|View full text |Cite
|
Sign up to set email alerts
|

Coordination geometry of lead carboxylates – spectroscopic and crystallographic evidence

Abstract: Despite their versatility, only a few single-crystal X-ray structures of lead carboxylates exist, due to difficulties with solubility. In particular, the structures of long-chain metal carboxylates have not been reported. The lone electron pair in Pb(ii) can be stereochemically active or inactive, leading to two types of coordination geometries commonly referred to as hemidirected and holodirected structures, respectively. We report (13)C and (207)Pb solid-state NMR and infrared spectra for a series of lead ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 46 publications
(71 reference statements)
4
62
0
Order By: Relevance
“…Solid‐state NMR spectroscopy probes the local structure around an NMR‐active nucleus (spin quantum number, I ≥ 1/2) and is sensitive to coordination number, bond lengths and local asymmetry. As such, it can be used to measure lone‐pair activity . We have previously reported the 207 Pb magic‐angle spinning (MAS) NMR spectroscopic behaviour of Pb[Au(CN) 2 ] – coordination polymers containing various nitrogen‐donor capping ligands, for which it was demonstrated that the anisotropic nature of the chemical shift could be correlated with structural distortion parameters that are associated with lone‐pair activity , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid‐state NMR spectroscopy probes the local structure around an NMR‐active nucleus (spin quantum number, I ≥ 1/2) and is sensitive to coordination number, bond lengths and local asymmetry. As such, it can be used to measure lone‐pair activity . We have previously reported the 207 Pb magic‐angle spinning (MAS) NMR spectroscopic behaviour of Pb[Au(CN) 2 ] – coordination polymers containing various nitrogen‐donor capping ligands, for which it was demonstrated that the anisotropic nature of the chemical shift could be correlated with structural distortion parameters that are associated with lone‐pair activity , …”
Section: Introductionmentioning
confidence: 99%
“…As such, it can be used to measure lone-pair activity. [14][15][16] We have previously reported the 207 Pb magic-angle spinning (MAS) NMR spectroscopic behaviour of Pb[Au(CN) 2 ]coordination polymers containing various nitrogen-donor cap-ping ligands, for which it was demonstrated that the anisotropic nature of the chemical shift could be correlated with structural distortion parameters that are associated with lone-pair activity. [14,16] The chemical-shift tensor describes the orientational dependence of the magnetic shielding, which depends on the local electronic environment and is generally anisotropic if the site symmetry is not cubic.…”
Section: Introductionmentioning
confidence: 99%
“…Since HCOO -is known to form metal-organic complex with Pb 2+ ,our working hypothesis was that the HCOO -influences the crystal growth of the perovskite interacting with Pb 2+ . [18] In Figure 1b, we depict a schematic view of the proposed mechanism: STEP To investigate the impact of the MAF on the crystal growth, we prepared perovskite precursor solutions with and without 5mol% of MAF. Perovskite films were prepared on SnO 2 deposited FTO substrates by spin coating the precursor solution in a nitrogen filled glovebox using the one-step anti-solvent method.…”
mentioning
confidence: 99%
“…The exploring speciation of Pb 2+ gains the special interest from chemists for understanding its coordination chemistry and structural effects . The variation in coordination properties of Pb 2+ depends on the size of the ligands and the nature of donor atoms thus it dictates the structural arrangements in the entire globe of metal–ligand complex systems.…”
Section: Introductionmentioning
confidence: 99%
“…The exploring speciation of Pb 2+ gains the special interest from chemists for understanding its coordination chemistry and structural effects. [1][2][3][4][5][6][7][8][9][10][11][12] The variation in coordination properties of Pb 2+ depends on the size of the ligands and the nature of donor atoms thus it dictates the structural arrangements in the entire globe of metal-ligand complex systems. In general, the distribution of coordination bonds to bulky ligands would follow the structural rearrangements to avoid the steric repulsion between them and occupied entire globe.…”
Section: Introductionmentioning
confidence: 99%